2022
DOI: 10.3390/batteries8100171
|View full text |Cite
|
Sign up to set email alerts
|

Li-Ion Battery Short-Circuit Protection by Voltage-Driven Switchable Resistance Polymer Layer

Abstract: Safety issues with lithium-ion batteries prevent their widespread use in critical areas of technology. Various types of protective systems have been proposed to prevent thermal runaway and subsequent battery combustion. Among them, thermoresistive systems, representing polymer composites that sharply increase their resistance when the temperature rises, have been actively investigated. However, they are triggered only when the heating of the battery has already occurred, i.e., the system undergoes irreversible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Electroactive polymer materials including conducting polymers and redox polymers have a growing influence on the direction of eco-friendly technology development, as they possess good environmental stability and electrical conductivity and have useful mechanical, optical and electronic properties and more. [1][2][3][4] Astonishing development of such materials leads to their wide application in many areas, such as the development of electrode materials and conductive binders for battery applications, [5][6][7][8][9][10] in chemical sensors, 11,12 supercapacitors, [13][14][15] (bio)microelectronics, [16][17][18] safety switches for Li-ion batteries [19][20][21] and so on. Some electroactive polymers and gels are found to be helpful in biomedical applications, especially in drug delivery, artificial tissue development and microfluidics.…”
Section: Introductionmentioning
confidence: 99%
“…Electroactive polymer materials including conducting polymers and redox polymers have a growing influence on the direction of eco-friendly technology development, as they possess good environmental stability and electrical conductivity and have useful mechanical, optical and electronic properties and more. [1][2][3][4] Astonishing development of such materials leads to their wide application in many areas, such as the development of electrode materials and conductive binders for battery applications, [5][6][7][8][9][10] in chemical sensors, 11,12 supercapacitors, [13][14][15] (bio)microelectronics, [16][17][18] safety switches for Li-ion batteries [19][20][21] and so on. Some electroactive polymers and gels are found to be helpful in biomedical applications, especially in drug delivery, artificial tissue development and microfluidics.…”
Section: Introductionmentioning
confidence: 99%
“…In recent reports from our group, 30,31 Beletskii et al proposed the use of a switchable-resistance layer of polymerized nickel salen complex, poly[Ni(CH 3 Osalen)], to protect LFP-based cathodes against overcharging. 30 The approach has garnered interest, with Li et al using a poly(3butylthiophene) layer that successfully protected an NCM811based electrode from overcharging to 4.9 V. 32 Unfortunately, the high onset potential of the resistance change led to unwanted processes in the electrolyte and to irreversible overoxidation of the polymer with significant loss of conductivity and subsequent device failure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As compared to the work of Li et al, the approach of Beletskii et al showed protection against short-circuiting as an additional benefit. 31 Poly[Ni(CH 3 Osalen)], which protected LiFePO 4 electrodes 30 by switching to a nonconducting state, is activated when the electrode potential exceeds 4.4 V vs Li/Li + , 33 making it a suitable candidate for protection of NMC-based materials, as the switching of poly[Ni(CH 3 Osalen)] films to nonconducting state conveniently coincides with the upper boundary of the NMC working potential window.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations